Transport of polycyclic aromatic hydrocarbons and pesticides during snowmelt within an urban watershed - Meyer, Torsten; Lei, Ying Duan; Wania, Frank (Water research (Oxford), 2011)
During snowmelt events in urban watersheds large amounts of organic contaminants are mobilized, potentially affecting the quality of surface and groundwater resources. The transport of polycyclic aromatic hydrocarbons (PAHs) and two pesticides in the highly urbanized Highland Creek watershed within the city of Toronto, Canada, was investigated by sampling river water during two snowmelt periods. The dissolved and the particulate fractions were separately extracted and analyzed. While during normal flow conditions levels of the sum of nine PAHs including phenanthrene, anthracene, fluoranthene, pyrene, benzo(b)fluoranthene, benzo(k)fluoranthene, benzo(a)pyrene, indeno(1,2,3-c,d)pyrene, and benzo(ghi)perylene ranged between 18 and 45ng/L, concentrations at the onset of melting varied from 550 to 4500ng/L. Considering enhanced stream discharge rates during snowmelt the contaminant flux in the river increased by three orders of magnitude. The intensity of the melt event largely determined the extent of the PAH concentration increase in the river. The relatively water soluble pesticides chlorothalonil and lindane (γ-HCH) also tended to appear early during melting. Their enrichment in river water may be influenced by the thickness of the snow pack at the onset of melting, and the mode of melt water ablation from the snow pack to the stream, i.e. whether it occurs by overland or sub-surface flow. ► Strong melt events correlate with elevated concentrations of particle-bound PAHs in river water. ► The PAH flux at the onset of melting exceeds the background chemical flux by three orders of magnitude. ► The pesticides lindane and chlorothalonil also tend to be released early during melting. ► Concentrations of both substances are low and likely reflect regional atmospheric background.